Man’s endless hunger for power and wealth - Abdul Razak, Mohd Abbas (Center for Community Development and Education (CCDE) Banda Aceh, 2025)
It seems that even the sky is not a limit for man. His insatiable hunger, his thirst for power and wealth, drives him to madness. Among all of God’s creations, man alone has never learned to say “enough.” Blinded by obsession, by the glitter of power and riches, he has committed the most heinous crimes and atrocities.